Exploring Swedish preschool teachers' perspectives on applying a self-reflection tool for improving inclusion in early childhood education and care - Ginner Hau, Hanna; Selenius, Heidi; Bjorck, Eva (Frontiers in Education, 2023)
In order to provide opportunities for high-quality early childhood education and care for each child, inclusive settings need to develop and sustain their potential to enable participation in terms of attendance and involvement for diverse groups of children. In 2015-2017, the European Agency for Special Needs and Inclusive Education completed a project on inclusive early childhood education, focusing on structures, processes, and outcomes that ensure a systemic approach to high-quality inclusive early childhood education. Within the project, a self-reflection tool for improving inclusion, the Inclusive Early Childhood Education Environment Self-Reflection Tool (ISRT), was developed. For purposes of future implementation of the ISRT, the present study focused on the teachers’ perspective regarding the ISRT’s potential to contribute to enabling all children’s participation, defined as attending and being actively engaged in the activities in early childhood education and care. The specific aim was to explore Swedish preschool teachers’ perceptions of the ISRT based on their experience of applying the tool. Twelve preschool teachers participated in semi-structured interviews about their experience of applying the tool. The interviews were analyzed with thematic analysis, which resulted in three main themes concerning the teachers’ perception of 1) the construction of the ISRT, 2) the time required for using the tool, and 3) the tool’s immediate relevance for practice. Each of these themes contained both negative and positive perceptions of the tool. Based on the negative and positive perceptions identified in the three main themes, future research and development of the ISRT in Swedish preschools are discussed. On a general level, the results are discussed in relation to the implementation of the ISRT in terms of acceptability, appropriateness, and feasibility.